Clinical experience and safety of Janus kinase inhibitors in giant cell arteritis: a retrospective case series from Sweden - Eriksson, Per; Skoglund, Oliver; Hemgren, Cecilia; Sjöwall, Christopher (Frontiers in Immunology, 2023)
The Janus kinase (JAK)-STAT signaling pathway is relevance in both Takayasu and giant cell arteritis (GCA), and the use of JAK-inhibitors (JAKi) in arthritis, psoriasis and inflammatory bowel disease is nowadays common. Some evidence of clinical efficacy of JAKi in GCA exists and a Phase-3 randomized-controlled-trial (RCT) of upadacitinib is currently recruiting. In 2017, we started using barcitinib in a GCA-patient with inadequate response to corticosteroids and have later treated another 14 GCA-patients with baricitinib/tofacitinib during intense follow-up. The retrospective data of these 15 individuals are here summarized. GCA was diagnosed based on the ACR criteria and/or imaging techniques combined with increased C-reactive protein (CRP) and/or erythrocyte sedimentation rate (ESR) followed by a good initial response to corticosteroids. JAKi was initiated based on inflammatory activity, with increased CRP, presumably dependent on GCA with clinical symptoms, despite unsatisfying high doses of prednisolone. Mean age at JAKi initiation was 70.1 years and mean exposure to JAKi was 19 months. From initiation, significant reductions in CRP were seen already at 3 (p=0.02) and 6 (p=0.02) months. A slower decrease was observed regarding ESR at 3 (p=0.12) and 6 (p=0.02) months. Furthermore, the daily prednisolone doses were reduced at 3 (p=0.02) and 6 (p=0.004) months. No GCA-relapses were observed. Two patients were affected by serious infections but JAKi-therapy was retained or reintroduced after recovery. We present encouraging observational data on JAKi in GCA in one of the hitherto largest case series with long-term follow-up. Our clinical experiences will complement results from the awaited RCT.